Trans-Cinnamaldehyde Inhibits IL-1β-Stimulated Inflammation in Chondrocytes by Suppressing NF-κB and p38-JNK Pathways and Exerts Chondrocyte Protective Effects in a Rat Model of Osteoarthritis. (8th May 2019) - Xia, Tianwei; Gao, Runzi; Zhou, Guowei; Liu, Jinzhu; Li, Jinsheng; Shen, Jirong
Abstract : Objective . Trans-cinnamaldehyde (TCA), a compound from Cinnamomum cassia Presl, has been reported to have anti-inflammatory effect. However, its effect on cartilage degradation in osteoarthritis is unclear. This study is designed to examine the effects of TCA on cartilage in vitro and in vivo. Material and Methods . SW1353 cells and human primary chondrocytes were treated with varying concentrations of TCA (2-20 μ g/ml) for 2 h followed by IL-1 β stimulation. Cell viability was examined by the MTT assay. Expression of MMP-1, MMP-3, MMP-13, ADAMTS-4, and ADAMTS-5 was examined by Western blot and RT-qPCR. Monosodium iodoacetate (MIA)-induced OA was established in rats to assess the chondrocyte protective effects of intraperitoneal injection of TCA (50 mg/kg). Results . TCA at a concentration of 10 μ g/ml had no significant effect on cell viability. MMP-1, MMP-3, MMP-13, ADAMTS-4, and ADAMTS-5 were decreased by TCA 2-10 μ g/ml in a dose-dependent manner (all P <0.05). Pretreatment with TCA decreased the degradation of I κ B α and increased the expression of p-I κ B α, indicating that NF- κ B inactivation was induced by TCA in IL-1 β -stimulated SW1353 cells. Pretreatment with TCA decreased the levels of p-p38 and p-JNK, while the levels of p-ERK were not significantly affected. TCA 10 μ g/ml significantly decreased expression levels of MMP-1, MMP-3, MMP-13, ADAMTS-4, and ADAMTS-5. In vivo results showed that TCA alleviated cartilage destruction and the OARSI scores. Conclusion . TCA possesses anti-inflammatory effect in vitro and exerts chondrocyte protective effects in vivo, in which NF- κ B and p38-JNK were involved.